Nurse Performance : Assessing The Roles Of Competence, Motivation and Commitment - Jusdijachlan Jusdijachlan; Susan Ridwan (Dinasti International Journal of Management Science, 2023)
To obtain various data collected which are analyzed and interpreted so as to obtain an overview of competency, motivation, commitment and performance as well as analyze the influence of competency, motivation and commitment on Nurse performance, both simultaneously and partially. The method used is a descriptive survey method and an explanatory survey. The type of investigation in this research is causality. Unit analysis of Dr. Lung Hospital Nurses. H. A. Rotinsulu Bandung City with a sample of 50 nurses. The time horizon in this research is cross sectional and the analysis methods used are frequency distribution and path analysis. The findings from this research are the motivation of nurses at Dr. Lung Hospital. H. A. Rotinsulu Bandung City is correct, Nurse competency is correct; according to needs, the existing commitment is good enough; Nurses' performance has high performance. Competence, motivation and commitment together influence the performance of Dr. Lung Hospital Nurses. H. A. Rotinsulu Bandung City. However, partially motivation is more dominant in influencing nurse performance than competence and commitment.